2019
DOI: 10.5713/ajas.18.0573
|View full text |Cite
|
Sign up to set email alerts
|

Rubber seed oil and flaxseed oil supplementation on serum fatty acid profile, oxidation stability of serum and milk, and immune function of dairy cows

Abstract: Objective This study was designed to investigate the effect of diet supplementation with rubber seed oil and flaxseed oil on serum fatty acids profile, oxidation stability of serum and milk, and immune function of dairy cows. Methods Forty-eight mid-lactation Holstein dairy cows were randomly assigned to one of four treatments for 8 wk, including basal diet (CON) or the basal diet supplemented with 4% rubber seed oil (RO), 4% flaxseed oil (FO) or 2% rubber seed oil plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…In this study, cows fed the HSO diets had a lower activity of SOD and GSH-Px than fed the CON diet, which indicated that the HSO diets can reduce the antioxidant capacity and increase the oxidative stress of dairy cows. This nding is in accordance with a previous report from Pi et al [69], who suggested that diet supplementation with rubber seed oil and axseed oil had a lower activity of CSH-Px in serum than that in cotrol group, whereas the SOD activity not affected dy dietary treatment.…”
Section: Plasma Metabolites and Oxidative Stress Parameterssupporting
confidence: 93%
“…In this study, cows fed the HSO diets had a lower activity of SOD and GSH-Px than fed the CON diet, which indicated that the HSO diets can reduce the antioxidant capacity and increase the oxidative stress of dairy cows. This nding is in accordance with a previous report from Pi et al [69], who suggested that diet supplementation with rubber seed oil and axseed oil had a lower activity of CSH-Px in serum than that in cotrol group, whereas the SOD activity not affected dy dietary treatment.…”
Section: Plasma Metabolites and Oxidative Stress Parameterssupporting
confidence: 93%
“…The n-3 PUFA content in milk can be influenced by the composition of the diet, and therefore flaxseed is the main source of n-3 PUFAs in diets used for dairy cows. Previous studies have shown that flaxseed supplementation can increase the concentration of n-3 PUFAs, particularly ALA, in milk [ 6 , 7 , 8 , 9 ] and plasma [ 10 ]. Flaxseed is rich in ALA; 18% of the total seed (dry matter [DM] basis) or 53–56% of the total fatty acid content in flaxseed is composed of ALA [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, addition of 3.5% or 4.5% rubber seed oil to the diet did not affect the production performance of laying hens, except for a declined abdominal fat percentage. In dairy cows, supplement of 40 g/kg rubber seed oil or flaxseed oil increased the functional fatty acids such as ALA, vaccenic acid and conjugated linoleic acid and decreased SFAs in milk fat, but with phospholipids, growth hormone, insulin and beta-hydroxybutyric acid in blood unchanged [ 13 ], and even enhanced their immune function [ 14 ]. Moreover, consumption of refined rubber seed oil proved to be safe and hypolipidemic in rhesus monkeys [ 15 ] and human beings [ 16 ].…”
Section: Discussionmentioning
confidence: 99%